Reduction of Nitroarenes Using CO and H2O in the Presence of a Nanostructured Cobalt Oxide/Nitrogen-Doped Graphene (NGr) Catalyst - Westerhaus, Felix A.; Sorribes, Iván; Wienhöfer, Gerrit; Junge, Kathrin; Beller, Matthias (Synlett, 2015)
The most common route to anilines is based on the reduction of the corresponding nitroarenes. In general, hydrogen is preferred as reducing agent and numerous catalytic systems are known to achieve such transformations. Besides, the use of CO/H2O as hydrogen source offers interesting possibilities for reductions. Carbon monoxide is a cheap and abundant chemical used on industrial scale for a variety of transformations. Although the reduction of nitroarenes with CO/H2O is known in the presence of noble-metal catalysts, earth-abundant inexpensive catalysts showing high selectivity have not yet been developed. In this respect, herein we present the use of a heterogeneous cobalt oxide catalyst (Co3O4/NGr@C), which is modified by nitrogen-doped graphene layers. Using this non-noble metal catalyst nitroarenes are reduced in high yields and good chemoselectivities.
Keywords: reduction; nitroarene; water-gas shift reaction; heterogeneous catalysis; cobalt